Facile aqueous synthesis of ZnCuInS/ZnS–ZnS QDs with enhanced photoluminescence lifetime for selective detection of Cu(ii) ions - Mgedle Nande; Aladesuyi Olanrewaju A.; Lebepe Thabang Calvin; Ncapayi Vuyelwa; Oluwafemi Oluwatobi Samuel (Green Processing and Synthesis, 2023)
Quaternary quantum dots (QDs) have recently gained more attention due to their low toxicity, tunable wavelength, reduced or no blueshift emission upon overcoating, improved photoluminescence (PL) quantum yield, and PL lifetime when compared to their binary (II–VI) and ternary (I–III–VI) counterparts. In this work, the aqueous synthesis of ZnCuInS/ZnS–ZnS multi-shell quaternary QDs as a nanosensor for the selective detection of Cu2+ ions was reported. The as-synthesized QDs were spherical, with a particle diameter of 3.66 ± 0.81 nm, and emitted in the first near-infrared window (725 nm) with an average decay PL lifetime of 43.69 ns. The X-ray diffraction analysis showed that the QDs were of the wurtzite structure, while the Fourier transform infrared spectroscopy confirmed GSH capping through the sulphur–metal bond. Furthermore, the fluorometric study shows that the developed multi-shell QDs were selective towards Cu2+ ions compared to other metal ions via fluorescence quenching with a limit of detection of 1.4 µM, which is below the acceptable limit in drinking water.